2020
DOI: 10.1002/eng2.12228
|View full text |Cite
|
Sign up to set email alerts
|

Structural health building response induced by earthquakes: Material softening and recovery

Abstract: Under proper loading conditions, micro-to-nanoscale heterogeneities (ie, the bond system) that are commonly found within the materials of a system can coalesce until causing macroscopic alterations of the system properties. The bond system is responsible for atypical and invariant-scale nonlinear elastic processes in granular media, from laboratory-tested materials (mm) to the Earth's crust (km). The unusual observed behavior involves slow recovery, or relaxation, of the elastic properties after dynamic loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Although a small permanent reduction in the natural frequencies of Caltech Hall has been observed for nondamaging historical earthquakes, the frequencies recover rapidly to their pre-event levels for the majority of events (Clinton et al, 2006). Such rapid dynamic softening (often termed anomalous nonlinear fast dynamics or ANFD) followed by slow recovery (often termed slow dynamics) has been widely documented in laboratory rock mechanics (tenCate et al, 2000;Johnson and Sutin, 2005) and recently reported for several structures (Kohler et al, 2005;Gueguen et al, 2016;Astorga et al, 2018;Astorga and Gueguen, 2020). Example spectrograms with a resolution of 12.8 s are plotted in Figure 4 for two earthquakes, showing that the apparent system frequencies of Caltech Hall drop suddenly at the onset of strong motion and then recover slowly following an approximately log-linear curve over the scale of minutes.…”
Section: Log-linear Recoverymentioning
confidence: 89%
“…Although a small permanent reduction in the natural frequencies of Caltech Hall has been observed for nondamaging historical earthquakes, the frequencies recover rapidly to their pre-event levels for the majority of events (Clinton et al, 2006). Such rapid dynamic softening (often termed anomalous nonlinear fast dynamics or ANFD) followed by slow recovery (often termed slow dynamics) has been widely documented in laboratory rock mechanics (tenCate et al, 2000;Johnson and Sutin, 2005) and recently reported for several structures (Kohler et al, 2005;Gueguen et al, 2016;Astorga et al, 2018;Astorga and Gueguen, 2020). Example spectrograms with a resolution of 12.8 s are plotted in Figure 4 for two earthquakes, showing that the apparent system frequencies of Caltech Hall drop suddenly at the onset of strong motion and then recover slowly following an approximately log-linear curve over the scale of minutes.…”
Section: Log-linear Recoverymentioning
confidence: 89%